2016
DOI: 10.1016/j.bbapap.2015.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Sialyltransferase inhibition and recent advances

Abstract: Sialic acids, existing as terminal sugars of glycoconjugates, play important roles in various physiological and pathological processes, such as cell-cell adhesion, immune defense, tumor cell metastasis, and inflammation. Sialyltransferases (STs) catalyze the transfer of sialic acid residues to non-reducing oligosaccharide chains of proteins and lipids, using cytidine monophosphate N-acetylneuraminic acid (CMP-Neu5Ac) as the donor. Elevated sialyltransferase activity leads to overexpression of cell surface sial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 49 publications
2
56
0
Order By: Relevance
“…Next, we determined whether compounds that alter N-glycan processing could promote EHT and HSPC overexpansion, similar to loss of miR-223. Briefly, we treated wild-type embryos undergoing EHT with swainsonine (SW) to enhance mannose-biased modification 37 , or a pan-sialyltransferase inhibitor (ST) to diminish terminal sialic acid incorporation 40 (Fig. 4 f-j and Supplementary Fig.…”
Section: Figurementioning
confidence: 99%
“…Next, we determined whether compounds that alter N-glycan processing could promote EHT and HSPC overexpansion, similar to loss of miR-223. Briefly, we treated wild-type embryos undergoing EHT with swainsonine (SW) to enhance mannose-biased modification 37 , or a pan-sialyltransferase inhibitor (ST) to diminish terminal sialic acid incorporation 40 (Fig. 4 f-j and Supplementary Fig.…”
Section: Figurementioning
confidence: 99%
“…Previous reports demonstrated that sialic acid is involved in various biological processes, including cell-cell adhesion, immune defence, tumour cell metastasis, and inflammation [710]. Increasing evidence has indicated that the ST8SIA family is associated with several human tumours.…”
Section: Introductionmentioning
confidence: 99%
“…Because hypersialylation in malignant cells has been shown to be a mechanism of immune evasion [59][60][61] , preclinical studies focusing on depleting tumor sialylation have developed several promising therapeutic strategies 62 . One such example is the fluorinated sialic acid analogue we used in our study, 3F-NeuAc.…”
Section: Discussionmentioning
confidence: 99%